The Guillermo Bermúdez Umaña’s composition at the Carabelas Building (1969-1972) (2021)
This article recalls the life of the architect Guillermo Bermúdez Umaña in the context of modern architecture in Colombia and analyzes the Las Carabelas building (1969-1972) based on the observation methodology of architectural projects focused on the components of the activity, the place, the form and the technique. The study, which is mostly graphic, displays the themes present in the Las Carabelas building in subdued red, which in turn are the design tools used by the architect in the composition of the building. In this way, the article acts as a catalog of practical tools that serve current and future architects in formalizing their specific designs.